Presence of chondroitin sulphate and requirement for heparan sulphate biosynthesis in the developing zebrafish inner ear - Jones, Ana A.; Diamantopoulou, Elvira; Baxendale, Sarah; Whitfield, Tanya T. (Frontiers in Cell and Developmental Biology, 2022)
Epithelial morphogenesis to form the semicircular canal ducts of the zebrafish inner ear depends on the production of the large glycosaminoglycan hyaluronan, which is thought to contribute to the driving force that pushes projections of epithelium into the lumen of the otic vesicle. Proteoglycans are also implicated in otic morphogenesis: several of the genes coding for proteoglycan core proteins, together with enzymes that synthesise and modify their polysaccharide chains, are expressed in the developing zebrafish inner ear. In this study, we demonstrate the highly specific localisation of chondroitin sulphate to the sites of epithelial projection outgrowth in the ear, present before any morphological deformation of the epithelium. Staining for chondroitin sulphate is also present in the otolithic membrane, whereas the otoliths are strongly positive for keratan sulphate. We show that heparan sulphate biosynthesis is critical for normal epithelial projection outgrowth, otolith growth and tethering. In the ext2 mutant ear, which has reduced heparan sulphate levels, but continues to produce hyaluronan, epithelial projections are rudimentary, and do not grow sufficiently to meet and fuse to form the pillars of tissue that normally span the otic lumen. Staining for chondroitin sulphate and expression of versican b, a chondroitin sulphate proteoglycan core protein gene, persist abnormally at high levels in the unfused projections of the ext2 mutant ear. We propose a model for wild-type epithelial projection outgrowth in which hyaluronan and proteoglycans are linked to form a hydrated gel that fills the projection core, with both classes of molecule playing essential roles in zebrafish semicircular canal morphogenesis.